Manajemen pendidikan sekolah inklusi untuk meningkatkan mutu hasil belajar anak berkebutuhan khusus (ABK) di SMP Negeri 15 Yogyakarta tahun pelajaran 21014/2015 - Rinawati Rinawati; Mundilarno Mundilarno (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
This research was aimed at discovering how far the inclusive school education management in Yogyakarta 15 State Junior High School managed to improve the quality of the learning results of disability students. The education management studied in the research included the planning, implementation, evaluation, obstacle identification and the efforts conducted by the school to improve the quality of the learning results in the academic year 2014-2015. This research was a qualitative type, and the data were collected was conducted bay interviews, observation, and documentation from the beginning to the end of the research. The sources of the data consist of the principle, the vice headmaster, the teachers, counselor teachers for disabled students, the school, and parents and regular students. The validity, reliability and objectivity data were triangulation. The research results showed that the school’s education management was quite good in terms of the implementation, evaluation, and solution for the arising problems. However, the planning for the students, the counselor's teacher to disability students, and the school’s infrastructures and facilities were not optimum yet. In more details, the research results are as follows:1) The planning was not optimum because the school could not admit students with mild slow-learning problems and students with mild mental handicaps because such was not yet regulated in the school’s student admission system. 2) The of instruction implementation ran very well, with satisfactory materials for disability students; and the learning interaction between regular students and the disability students was very conducive. 3) The inclusive school education evaluation was implemented quite well. The evaluation materials were adapted to the condition of the disabled students. The curriculum evaluation was conducted at least once a year. 4) The obstacle was that the government did not provide enough infrastructures and facilities and counselor teachers for disability.students 5) To overcome the obstacle for students disability. But the school could maximize the help from regular students, the regular teachers, and the administrative staff.